Unraveling the skin; a comprehensive review of atopic dermatitis, current understanding, and approaches - Afshari, Moeina; Kolackova, Martina; Rosecka, Michaela; Čelakovská, Jarmila; Krejsek, Jan (Frontiers in Immunology, 2024)
Atopic dermatitis, also known as atopic eczema, is a chronic inflammatory skin disease characterized by red pruritic skin lesions, xerosis, ichthyosis, and skin pain. Among the social impacts of atopic dermatitis are difficulties and detachment in relationships and social stigmatization. Additionally, atopic dermatitis is known to cause sleep disturbance, anxiety, hyperactivity, and depression. Although the pathological process behind atopic dermatitis is not fully known, it appears to be a combination of epidermal barrier dysfunction and immune dysregulation. Skin is the largest organ of the human body which acts as a mechanical barrier to toxins and UV light and a natural barrier against water loss. Both functions face significant challenges due to atopic dermatitis. The list of factors that can potentially trigger or contribute to atopic dermatitis is extensive, ranging from genetic factors, family history, dietary choices, immune triggers, and environmental factors. Consequently, prevention, early clinical diagnosis, and effective treatment may be the only resolutions to combat this burdensome disease. Ensuring safe and targeted drug delivery to the skin layers, without reaching the systemic circulation is a promising option raised by nano-delivery systems in dermatology. In this review, we explored the current understanding and approaches of atopic dermatitis and outlined a range of the most recent therapeutics and dosage forms brought by nanotechnology. This review was conducted using PubMed, Google Scholar, and ScienceDirect databases.